Evaluation of concordance between the microorganisms detected in the nasopharynx and middle ear of children with otitis media - van Dongen, Thijs M A; van der Heijden, Geert J M G; van Zon, Alice; Bogaert, Debby; Sanders, Elisabeth A M; Schilder, Anne G M (The Pediatric infectious disease journal, 2013)
Studies of microorganisms involved in otitis media in children often use a nasopharyngeal sample as a proxy for the middle ear fluid to test for bacteria and viruses. The question is whether such studies provide an accurate estimate of the prevalence of microorganisms involved in otitis media. We performed a systematic review of the literature reporting on the concordance between test results of nasopharyngeal and middle ear fluid samples for the most prevalent microorganisms in children with otitis media. Our findings show that the concordances vary from 68% to 97% per microorganism. For the most prevalent microbes, positive predictive values are around 50%. Most negative predictive values are moderate to high, with a range from 68% up to 97%. These results indicate that test results from nasopharyngeal samples do not always provide an accurate proxy for those of the middle ear fluid. It is important to interpret and use results of such studies carefully.